Raporturile Parlamentului cu serviciile de informații - Daniel BUDA; Dacian Grațian GAL (Revista Transilvană de Ştiinţe Administrative, 2005)
Our trial refers to the rapports of the legislative power with the information services, analyzes the Romanian realities and the ones of other western democratic states, mostly European states. These rapports are to be found in the control function register, function exercised by the Parliament and its functioning mechanisms, as well as the institutional realities, which differ from one state to another. The supervision and the parliamentary control over the information services prove the existence of a supervision model with a regulation statute established by law, and that of a limited supervision model. The object of parliamentary control over the information services is the provision of the state law by these services and especially the provision of the specific law, which establishes the functioning of these services.